Knowledge, attitudes, and practices regarding sterilization protocol among undergraduate dental students in Faridabad City: A questionnaire-based study - Akshat Sachdeva; Aditi Sharma; Sumit Bhateja; Geetika Arora (Wolters Kluwer Medknow Publications, 2019)
Aim: To assess the level of knowledge, attitudes, and practices regarding sterilization/infection control measures among undergraduate dental students. Materials and Methods: A total of 300 dental students from Manav Rachna Dental College, Faridabad, Haryana participated in this study. A questionnaire survey comprising 24 questions regarding knowledge, attitudes, and practices was completed by the participants. Results: It was observed that a majority of the students were highly concerned regarding the sterilization and infection control protocol. 96.9% students dispose of their gloves after use. About 89% are aware of the exact specifications of sterilization via autoclave. Use of mouth masks and head caps as effective infection control measures was practiced among 82.4% students. A large fraction of students comprising about 85% believed that proper sterilization could not be achieved by simple boiling of instruments. Conclusion: The level of knowledge and attitude of sterilization measures were acceptable, although compliance and practice of the same needs to be more worked upon.